2019
DOI: 10.3389/fpsyg.2019.02540
|View full text |Cite
|
Sign up to set email alerts
|

Information-Sharing Behavior on WeChat Moments: The Role of Anonymity, Familiarity, and Intrinsic Motivation

Abstract: Information-sharing behavior is affected by identity recognition perception. The current study aims to delve into the impact of familiarity and anonymity on information-sharing behavior, and the mediating role of intrinsic motivations on WeChat Moments. We hypothesized a mediator role of intrinsic motivations in the relationship between an individual’s perceptions and information sharing. Based on the self-determination theory, a model was created and tested using a sample of 531 frequent users. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 131 publications
(186 reference statements)
0
27
0
1
Order By: Relevance
“…Some identity information can be identified by at least their real name or their picture, while other things like blurred picture and nickname may only provide limited information about the user. At some point, the world of SNSs reveals users' real social identities and leads to a healthy exchange of content, whereas perceived anonymity of self-decreases the ability of users to share information [39]. The researcher has also found that a higher degree of perceived anonymity on SNSs means less need to reveal self [40].…”
Section: ) Perceived Anonymity Of Selfmentioning
confidence: 99%
“…Some identity information can be identified by at least their real name or their picture, while other things like blurred picture and nickname may only provide limited information about the user. At some point, the world of SNSs reveals users' real social identities and leads to a healthy exchange of content, whereas perceived anonymity of self-decreases the ability of users to share information [39]. The researcher has also found that a higher degree of perceived anonymity on SNSs means less need to reveal self [40].…”
Section: ) Perceived Anonymity Of Selfmentioning
confidence: 99%
“…The results of participation affect public decision-making or governance behaviors. Researchers have studied the impact of cyber anonymity on self-disclosure and information sharing (Yoon and Rolland, 2012;Chen et al, 2016Chen et al, , 2019b.…”
Section: Cyber Anonymity and Online Public Opinionmentioning
confidence: 99%
“…Social recognition such as respect and reputation are intrinsic rewards, whereas economic reward is an extrinsic reward. Researchers propose that intrinsic [21,22] and extrinsic rewards [23] are two of the main influencing factors in knowledge sharing. On these bases, we propose hypotheses 2 and 3:…”
Section: Intrinsic and Extrinsic Rewardsmentioning
confidence: 99%